Attitude Certainty and Conflict Style: Divergent Effects of Correctness and Clarity. (July 2014) - Rios, Kimberly; DeMarree, Kenneth G.; Statzer, Johnathan
Little research has examined the properties of people's attitudes that predict how they will respond to conflict with others whose opinions differ. We propose that one aspect of attitude certainty—attitude correctness, or the perception that one's attitude is the "right" attitude to have—will predict more competitive conflict styles. This hypothesis was tested across five data sets comprising four studies. In Studies 1a and 1b, perceptions of attitude correctness (but not another form of attitude certainty, attitude clarity) predicted participants' tendencies to send competitive messages to an ostensible partner who held the opposite opinion. In Studies 2 to 4, manipulations of attitude correctness, but not attitude clarity (Study 3), also increased competitiveness in conflict, and perceived correctness mediated the effect of the correctness manipulation on conflict style (Study 4). The present research has implications for both the predictors of conflict style and the consequences of different forms of attitude certainty.